Fissures in standards formulation: The role of neoconservative and neoliberal discourses in justifying standards development in Wisconsin and Minnesota. - Samantha Caughlan; Richard Beach (Arizona State University, 2007)
An analysis of English/language arts standards development in Wisconsin and Minnesota in the late 1990s and early 2000s shows a process of compromise between neoliberal and neoconservative factions involved in promoting and writing standards, with the voices of educators conspicuously absent. Interpretive and critical discourse analyses of versions of English/language arts standards at the high school level and of public documents related to standards promotion reveal initial conflicts between neoconservative and neoliberal discourses, which over time were integrated in final standards documents. The content standards finally released for use in guiding curriculum in each state were bland and incoherent documents that reflected neither a deep knowledge of the field nor an acknowledgement of what is likely to engage young learners. The study suggests the need for looking more critically at standards as political documents, and a greater consideration of educators' expertise in the process of their future development and revision.